Práticas de correção e aprendizagem: produção de subjetividades na contemporaneidade - Morgenstern, Juliane Marschall (Universidade do Vale do Rio dos Sinos, 2016)
Taking as reference the growing programs of age-grade flow correction and Accelerated Learning currently disclosed in Brazil, this research aims to discuss how the correction practices operate and their effects on contemporary world. More specifically, the operation of correction practices and their effects are analyzed in the Brazilian education nowadays. Although the materials mobilized for the preparation of this Thesis has been quite broad, to carry out the research the corpus was composed from the teaching materials and the systematization of school flow programs that work for accelerated learning, produced in Brazil, since the 1990s. Twenty depositions of subjects that integrate program activities and discuss their experiences also make up the corpus. It was found a shift in the ways of correction practices in recent decades, whose centrality turns to the regulation of school flow and not to an individual body orthopedics. Analyses conducted the investigation for the descent of corrective practices in a temporally broader context, which was accomplished through a historicizing of genealogical inspiration. In tracing a panoramic map, were found four distinct acting emphases with regard to the purpose (télos) of the correction modes. The first emphasis is located in the context of Pagan Antiquity; the second emphasis is found in Christian Antiquity; the third, in the unfolding of the disciplinary technologies introduced in Modernity; and the fourth emphasis concerns the actions of security technologies, whose evidence is visible in Contemporaneity. It found also that, in its mode of operation, the contemporary corrective practices converge with the creation of a learning subjectivity (Homo discentis), produced in the late 19th century to the 20th century. Under the conditions of learning through life (lifelong learning), there is a redirecting on correction practices, whose prominence is directed to the construction of subjectivities that become self-fulfilling. The productivity of these practices became visible when positioning the learner under certain conditions, producing him as a subjectivity invested by acceleration. Thus, it was found that the individual subjectivized to lifelong learning should be able to correct itself in any circumstances and at any time, in order to adjust himself to a world where change is constant. Such as the possibility to act on itself and being active is put as a condition that has always been present in the actions practiced by students, to these students was also implicated the condition to be corrected or to correct itself. It was found that the correction is present as something permanent and necessary in the constitution of a learning subjectivity.
Keywords: Práticas de correção; Subjetivação; Governamentalidade; Aprendizagem; Correction practices; Subjectivation; Governmentality; Learning; ACCNPQ::Ciências Humanas::Educação